2020
DOI: 10.7717/peerj.9357
|View full text |Cite
|
Sign up to set email alerts
|

Host transcriptome-guided drug repurposing for COVID-19 treatment: a meta-analysis based approach

Abstract: Background Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been declared a pandemic by the World Health Organization, and the identification of effective therapeutic strategy is a need of the hour to combat SARS-CoV-2 infection. In this scenario, the drug repurposing approach is widely used for the rapid identification of potential drugs against SARS-CoV-2, considering viral and host factors. Methods We adopted a host transcriptome-based drug rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 60 publications
0
40
1
Order By: Relevance
“…In comparison with other studies which employed similar computational approach for drug repurposing based on transcriptome reversal [ 27 , 28 , 29 , 31 ], we observed only a minor or no overlap of the drug candidate lists. Shared candidates were ADRA1B antagonists (nortriptyline in our study), as well as ACE inhibitor perindopril and NR1I2 agonists (econazole and ritonavir in our study) that were also identified by El-Hachem et al [ 30 ].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In comparison with other studies which employed similar computational approach for drug repurposing based on transcriptome reversal [ 27 , 28 , 29 , 31 ], we observed only a minor or no overlap of the drug candidate lists. Shared candidates were ADRA1B antagonists (nortriptyline in our study), as well as ACE inhibitor perindopril and NR1I2 agonists (econazole and ritonavir in our study) that were also identified by El-Hachem et al [ 30 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Several in silico drug repurposing studies based on a transcriptome reversal approach have already been published in the context of COVID-19 [ 27 , 28 , 29 , 30 , 31 ]. However, one common issue in such studies is a complete lack or insufficiency of the criteria for inclusion of datasets in the analysis which may then produce misleading results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scale and cost of this global health crisis is such that effective drug therapies have an important and complementary role to play in treating this disease. In recent months, in silico studies have identified putative repurposable drugs for treating COVID-19 20 , 50 , 74 – 77 . Many of these studies exploit the finding that SARS-CoV-2 may enter the cell by binding to angiotensin converting enzyme 2 (ACE2) 78 and utilize a combination of structural and biomedical data to identify drug candidates 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to virus-centered antiviral strategy that targets viral genes to directly interfere with virus reproduction and infection, a host-centered antiviral approach has several advantages such as (1) functional host genes are more conserved and evolutionally stable than viral genes, which makes host-targeting drugs more tolerant to frequent viral mutations than those virus-targeting counterparts; 2) different viruses may share a similar set of host genes during certain stages of viral life cycle, which underlines the basis of developing broad-spectrum antivirals so that one host-targeting drug may treat multiple virus infection; and (3) there are significantly more targeted drugs approved for host genes than those for viral genes, thus likely increasing the success rate of drug repurposing by adopting host-centered strategy. Previous studies have extensively tried targeting host genes for developing antiviral solutions ( Ackerman et al., 2018 ; Bosl et al., 2019 ; Li et al., 2019 ; Loganathan et al., 2020 ; Luo et al., 2017 ; Saiz et al., 2018 ; Zhou et al., 2020 ). Host receptors mediating viral entrance into the cells represent the most popular host targets for drugs to block viral infection.…”
Section: Discussionmentioning
confidence: 99%